Budaya Belajar Mandiri dan Berkelanjutan: Strategi Pengembangan Kompetensi PNS di Pemerintah Kota Tangerang - Maulana, Ayi; Silitonga, Mala Sondang; Asropi (Jurnal Ilmiah Administrasi Publik, 2023)
This study was conducted to look factors that influence and look for strategy of self-development and continuous learning culture in fulfilling the competency development of Civil Servants in. Tangerang City Government. The method used with qualitative methods is a descriptive approach. Primary data were obtained from in-depth interviews with key-informants and secondary data from books, journals and related regulations. The results of the research establishing a systemized learning organization such as a Corporate University that can set development goals and track learning progress are important to strengthen the organization roles in Tangerang City Government. The organization also needs to encourage supervisor roles and shape individual characteristics. In addition to the 3 aspects of the London and Smither model, there are also opportunities and challenges for self-development and continuous learning culture in the form of regulation, collaboration with other organizations, demands for public trust and adaptation of society era 5.0.